REPRESENTASI DAMPAK KEKERASAN SEKSUAL DALAM FILM “GEORGIA” (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) - Safrina, Azwa; Firmannandya, Ade (Universitas Negeri Surabaya, 2025)
AbstractThis study aims to examine the representation of the impact of sexual violence in the film Georgia in 11 film scenes analyzed and classified according to the impacts of sexual violence experienced by the victim's parents. This research uses Charles Sanders Peirce's semiotic analysis which consists of three interconnected elements, including representament or sign, object, interpretant or interpreter. The results obtained show that the impact of sexual violence is classified into three main topics. First, psychological distress such as feelings of guilt, self-blame, shame, helplessness, anger, anxiety, feeling like a failure as a parent, confusion, shock, distrust, hopelessness, and sadness. Second, the creation of relationship tensions with others such as distrust of others. Third, financial problems such as debt and loan defaults. In addition, Georgia's film also shows the impact of the social environment in viewing and treating victims and families of victims of sexual violence, which is divided into two main topics, namely stigmatization and discrimination, as well as exclusion and marginalization.